The impact of control strategies and behavioural changes on the elimination of Ebola from Lofa County, Liberia. (26th May 2017) - Funk, Sebastian; Ciglenecki, Iza; Tiffany, Amanda; Gignoux, Etienne; Camacho, Anton; Eggo, Rosalind M.; Kucharski, Adam J.; Edmunds, W. John; Bolongei, Josephus; Azuma, Phillip; Clement, Peter; Alpha, Tamba S.; et al.
Abstract : The Ebola epidemic in West Africa was stopped by an enormous concerted effort of local communities and national and international organizations. It is not clear, however, how much the public health response and behavioural changes in affected communities, respectively, contributed to ending the outbreak. Here, we analyse the epidemic in Lofa County, Liberia, lasting from March to November 2014, by reporting a comprehensive time line of events and estimating the time-varying transmission intensity using a mathematical model of Ebola transmission. Model fits to the epidemic show an alternation of peaks and troughs in transmission, consistent with highly heterogeneous spread. This is combined with an overall decline in the reproduction number of Ebola transmission from early August, coinciding with an expansion of the local Ebola treatment centre. We estimate that healthcare seeking approximately doubled over the course of the outbreak, and that isolation of those seeking healthcare reduced their reproduction number by 62% (mean estimate, 95% credible interval (CI) 59–66). Both expansion of bed availability and improved healthcare seeking contributed to ending the epidemic, highlighting the importance of community engagement alongside clinical intervention. This article is part of the themed issue 'The 2013–2016 West African Ebola epidemic: data, decision-making and disease control'.